The treatment of epilepsy in developing countries: where do we go from here? - Scott Robert A.; Lhatoo Samden D.; Sander Josemir W.A.S (The World Health Organization, 2001)
Epilepsy is the most common serious neurological disorder and is one of the world?s most prevalent noncommunicable diseases. As the understanding of its physical and social burden has increased it has moved higher up the world health agenda. Over four-fifths of the 50 million people with epilepsy are thought to be in developing countries; much of this condition results from preventable causes. Around 90% of people with epilepsy in developing countries are not receiving appropriate treatment. Consequently, people with epilepsy continue to be stigmatized and have a lower quality of life than people with other chronic illnesses. However, bridging the treatment gap and reducing the burden of epilepsy is not straightforward and faces many constraints. Cultural attitudes, a lack of prioritization, poor health system infrastructure, and inadequate supplies of antiepileptic drugs all conspire to hinder appropriate treatment. Nevertheless, there have been successful attempts to provide treatment, which have shown the importance of community-based approaches and also indicate that provision for sustained intervention over the long term is necessary in any treatment programme. Approaches being adopted in the demonstration projects of the Global Campaign Against Epilepsy - implemented by the International League Against Epilepsy, the International Bureau for Epilepsy, and the World Health Organization - may provide further advances. Much remains to be done but it is hoped that current efforts will lead to better treatment of people with epilepsy in developing countries.